2014
DOI: 10.1586/14789450.2014.971762
|View full text |Cite
|
Sign up to set email alerts
|

Improved understanding of pathogenesis from protein interactions inMycobacteriumtuberculosis

Abstract: Comprehensive mapping and analysis of protein-protein interactions provide not only systematic approaches for dissecting the infection and survival mechanisms of pathogens but also clues for discovering new antibacterial drug targets. Protein interaction data on Mycobacterium tuberculosis have rapidly accumulated over the past several years. This review summarizes the current progress of protein interaction studies on M. tuberculosis, the causative agent of tuberculosis. These efforts improve our knowledge on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…tuberculosis results mostly in chronic, latent infection without clinical symptoms, but a small number of patients move on to develop active TB. Other than the lack of T cell function, which drives active TB especially in HIV-patients, the factors determining predisposition to the progression to active TB are not well understood although several clinical conditions predispose to active TB [2,3]. TB has many extrapulmonary manifestations, with bone and joint involvement being the most common (10–11% of extrapulmonary TB) [4].…”
Section: Introductionmentioning
confidence: 99%
“…tuberculosis results mostly in chronic, latent infection without clinical symptoms, but a small number of patients move on to develop active TB. Other than the lack of T cell function, which drives active TB especially in HIV-patients, the factors determining predisposition to the progression to active TB are not well understood although several clinical conditions predispose to active TB [2,3]. TB has many extrapulmonary manifestations, with bone and joint involvement being the most common (10–11% of extrapulmonary TB) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous study demonstrated that the interaction of the molecular chaperone protein GroEL with Tuf (the translation extension factor) plays an important role in the survival of M. tuberculosis . DnaK was a component of the surface of M. tuberculosis and is accessible on the surface of cultured bacilli .…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics and metabolomics Although still in early stages, the field of proteomics and metabolomics with respect to TB shows promise [166][167][168]. Sandhu et al generated mass spectrometry proteomic fingerprints that could successfully distinguish active TB from symptomatic controls in patients presenting to a Peruvian clinic [169].…”
Section: Transcriptomicsmentioning
confidence: 99%